PENGARUH METODE PEMBELAJARAN DENGAN TUTOR TEMAN SEBAYA UNTUK MATA KULIAH PROMOSI KESEHATAN - Rita Rena Pudyastuti (Poltekkes Kemenkes Maluku, 2017)
Learning method approach is one element of increasing student achievement index. In this study will be more focused on efforts to overcome the causes of the low learning outcomes of third semester students of the second semester in the Health Promotion course in the Department of Nursing Ambon. The method used in this research is Quasi Experimental. The population in this study were students of Maluku Health Ministry Polytechnic. The sample in this study was the third semester students of the Department of Nursing at the Maluku Ministry of Nursing. Based on the results of the research, Health Promotion learning outcomes using peer tutor learning models are more effective than learning using conventional learning models in terms of improving learning outcomes. This is shown from the results of the t test or the two average difference test where the difference in the average gain value of the experiment with the average gain control value is 0.47 - 0.32 = 0.15, and when interpreted the gain value is relatively low, then from the results of the t test obtained t count = 17.94> t table (2.048) which means H1 is accepted. So it can be concluded that there are significant changes between student learning outcomes before and after using peer tutoring learning models in learning Health Promotion. Keywords: Learning methods, peer friend tutors, health promotion